An effective method to optimise plasma immersion ion implantation: Sensitivity analysis and design based on low‐density polyethylene. Issue 6 (28th February 2022) - Chen, Yuan; Xu, Can; Wang, Chun‐Hui; Bilek, Marcela M. M.; Cheng, Xinying
Abstract: The performance of polymer surface treatment using plasma immersion ion implantation (PIII) depends on many operating parameters, such as treatment duration, radiofrequency power, pulsed bias voltage and pulse repetition rate, and the ion fluence applied on the polymer surface. Currently, the identification of optimal operating parameters to achieve specific performance targets is heavily based on trail and error with extensive experimental testing. Herein, we present an optimisation method based on sensitivity analysis using polynomial chaos expansion and experimental design with Kriging surrogate model to greatly reduce the amount of experiments. The combined effects of PIII operating parameters on low‐density polyethylene surface modifications are investigated, demonstrating the validation and effectiveness of the method and design. The new approach offers highly accurate and computationally efficient way for achieving optimum radical density, wettability and optical transmittance that are important for biomedical applications. Abstract : We present an effective mathematic method to study the effect of plasma immersion ion implantation (PIII) operating parameters on the properties of a polymer surface and determine the optimal combination of PIII parameters experimentally dependent on the materials and applications. The results show that the polynomial chaos expansion‐based optimisation can achieve the optimal solution with the preferred properties of a polymer surface.